Preference and development of Tribolium castaneum (Herbst, 1797) (Coleoptera: Tenebrionidae) in whole grain and flour form of five corn varieties - Ludji Pantja Astuti; YUNITA EKA LESTARI; RINA RACHMAWATI; Mutalaliah (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Astuti LP, Lestari YA, Rachmawati R, Mutala’liah. 2020. Preference and development of Tribolium castaneum (Herbst, 1797) (Coleoptera: Tenebrionidae) on whole grain and flour form of five corn varieties. Biodiversitas 21: 564-569. Red flour beetle can cause detrimental loss on stored corn during storage period. The usual forms of stored corn are whole grain and flour form. However, the information about the infestation on both form of stored corn is limited, therefore this research aims to investigate the feeding preference and development of Tribolium castaneum on various corn varieties (Pioneer 21, Pioneer 29, Pertiwi 3, Bisi 18, and Bisma) in whole grain and flour form. The research was conducted on Plant Pest Laboratory, Department of Plant Pests and Diseases, University of Brawijaya from February until March 2016. The feeds for treatment were Pioneer 21, Pioneer 29, Pertiwi 3, Bisi 18, and Bisma in whole grain and flour form. The observed variables were the adult presence, adult mortality, the number of eggs, larvae, pupae, F1 progeny emerged, the developmental period of eggs, larvae, and pupae, egg-adult, and life cycle. Data analyzed by ANOVA and followed by LSD at 5%. The results showed that T. castaneum was more preferred to colonize and oviposition in Pioneer 21 flour than others i.e. 13.33 adults and 145 eggs. Similarly, on the population growth of T. castaneum, the highest number of eggs, larvae, pupae, and F1 progeny emerged was on Pioneer 21 flour i.e. 196 eggs, 179.67 larvae, 83.67 pupae, and 73.33 adults, respectively. Moreover, the fastest developmental period of egg, larva, and pupa, egg-adult and life cycle was also in Pioneer 21 flour i.e., 5.5, 26.77, 5.97, 38.23, and 41.87 days, respectively. Pioneer 21 corn variety has high protein content, therefore it is suitable for T. castaneum development.